TREVOR OWENS, The Theory and Craft of Digital Preservation - McLellan, Evelyn (Archivaria, 2019)
The Theory and Craft of Digital Preservation. Trevor Owens. Baltimore: Johns Hopkins University Press, 2018. 226 pp. ISBN 978-1421426976